HUKUM PIDANA, DEMOKRASI DAN HAM - Didik Endro Purwoleksono (Perspektif, 2003)
Speaking of law is always connected with democracy and human rights as an integrated component. Law is described as a frame or legalization of democracy, while democracy it self is a part of human rights, furthermore, human rights need to be constructed as a specific law.